Amplitude variability in γ Dor and δ Sct stars observed by the Kepler spacecraft. Issue Volume 11:Issue A29B(2015) (27th October 2016) - Guzik, Joyce A.; Kosak, Katie; Bradley, Paul A.; Jackiewicz, Jason
Abstract: The NASA Kepler spacecraft data revealed a large number of multimode nonradially pulsating γ Dor and δ Sct variable star candidates. The Kepler high precision long time-series photometry makes it possible to study amplitude variations of the frequencies. We summarize recent literature on amplitude and frequency variations in pulsating variables. We are searching for amplitude variability in several dozen faint γ Doradus or δ Scuti variable-star candidates observed as part of the Kepler Guest Observer program. We apply several methods, including a Matlab-script wavelet analysis developed by J. Jackiewicz, and the wavelet technique of the VSTAR software (http://www.aavso.org/vstar-overview ). Here we show results for two stars, KIC 2167444 and KIC 2301163. We discuss the magnitude and timescale of the amplitude variations, and the presence or absence of correlations between amplitude variations for different frequencies of a given star. Amplitude variations may be detectable using Kepler data even for stars with Kepler magnitude > 14 with low-amplitude frequencies ( 100 ppm) using only one or a few quarters of long-cadence data. We discuss proposed causes of amplitude spectrum variability that will require further investigation.